Risk sharing and portfolio allocation in EMU - Demyanyk, Yulina; Ostergaard, Charlotte; Sorensen, Bent E.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission: Directorate-General for Economic and Financial Affairs, 2008)
This paper investigates whether risk sharing, measured as income and consumption smoothing, among countries in the EU and the European Economic and Monetary Union (EMU) has increased since the adoption of the euro. We ask:•Have the recent increase in foreign equity and debt holdings been associated with more risk sharing? •Do certain classes of assets (debt, equity, foreign direct investment) provide relatively more or less risk sharing? •Do liabilities provide risk sharing differently from assets? •Do investments in EMU countries provide more or less risk sharing per euro invested compared to investments in non-EMU countries?•Has increased banking integration improved risk sharing? Due to the short span of years since the introduction of the euro, our results are tentative, but they indicate that the monetary union has facilitated risk sharing, although the level of risk sharing is still much below the level found among U.S. states.
Economic Papers.